2019
DOI: 10.21873/anticanres.13195
|View full text |Cite
|
Sign up to set email alerts
|

Upfront Cranial Radiotherapy Followed by Erlotinib Positively Affects Clinical Outcomes of Epidermal Growth Factor Receptor-mutant Non-small Cell Lung Cancer With Brain Metastases

Abstract: Background/Aim: The optimal treatment strategy for epidermal growth factor receptor (EGFR)-mutant nonsmall cell lung cancer (NSCLC) patients with brain metastasis (BM) has not yet been fully determined. The aim of this study was to investigate the optimal management of EGFR-mutant NSCLC patients with BM. Patients and Methods: A multicenter retrospective study was performed on the clinical outcomes of 81 advanced/recurrent EGFR-mutant NSCLC patients with BM treated with EGFR-tyrosine kinase inhibitors (EGFR-TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…However, direct comparison with the current study seems to be di cult because some of these ones analyzed patient cohorts treated with WBRT alone [18] or including second or further line of EGFR-TKI therapy [8,19]. Upfront EGFR-TKI may be a useful option for certain subgroups of EGFR-mutant NSCLC patients with BM such as those having no CNS symptom or a smaller number of BM lesions, given its antitumor activity in BM in addition to extracranial lesions [5,7,20]. Furthermore, the initiation of systemic treatment is not delayed with the avoidance of potential toxicity of local treatment [1].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, direct comparison with the current study seems to be di cult because some of these ones analyzed patient cohorts treated with WBRT alone [18] or including second or further line of EGFR-TKI therapy [8,19]. Upfront EGFR-TKI may be a useful option for certain subgroups of EGFR-mutant NSCLC patients with BM such as those having no CNS symptom or a smaller number of BM lesions, given its antitumor activity in BM in addition to extracranial lesions [5,7,20]. Furthermore, the initiation of systemic treatment is not delayed with the avoidance of potential toxicity of local treatment [1].…”
Section: Discussionmentioning
confidence: 94%
“…The most controversial issue in the management of EGFR-mutant NSCLC with BM is the incorporation of local treatment. Although many retrospective studies showed con icting results [5][6][7][8][15][16][17][18][19][20], a few meta-analyses revealed better OS by addition of local treatment [2,21,22]. Furthermore, a large retrospective study from the United States demonstrated improved OS using upfront local treatment compared with EGFR-TKI alone [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the retrospective study by Magnuson et al [21] demonstrated inferior OS with deferral of brain radiotherapy. Upfront BRT followed by TKI may be an appropriate initial management approach for EGFR-mutant NSCLC patients with BM [22] .…”
Section: / 23mentioning
confidence: 99%
“…However, the retrospective study by Magnuson et al [ [21] ] demonstrated inferior OS with deferral of BRT. Another study reported that upfront BRT followed by TKI therapy may be an appropriate initial management approach for EGFR-mutant NSCLC patients with BM [ [22] ] .…”
Section: Introductionmentioning
confidence: 99%